PENGEMBANGAN MEDIA FLASHCARD BERBANTUAN AUGMENTED REALITY PADA MATERI WILAYAH NKRI UNTUK MENINGKATKAN KETERLIBATAN BELAJAR SISWA KELAS VII UPT SMP NEGERI 29 MEDAN - Cahya, Mira; Batubara, Abidunur; Yunita, Sri; Siagian, Liber; Habeahan, Sampitmo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology requires innovation in learning to create interactive and engaging learning experiences. However, Civic Education learning is still dominated by conventional methods and limited learning media, resulting in low student engagement. This study aimed to develop Augmented Reality-assisted flashcard media on the topic of the Territory of the Unitary State of the Republic of Indonesia (NKRI), determine its feasibility, and identify student engagement after its implementation. This research employed a Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects were seventh-grade students at UPT SMP Negeri 29 Medan. Data were collected through observation, interviews, questionnaires, and documentation. The results showed that the media was categorized as very valid based on material expert validation (84%) and media expert validation (86%). Practicality testing by teachers obtained 90%, while student responses reached 88%. The media successfully increased behavioral, emotional, and cognitive engagement. Therefore, Augmented Reality-assisted flashcard media is feasible and practical for Civic Education learning.